Shoulder and elbow overuse injuries in youth sports - Long, Janan Shiwei (2016)
Purpose: To provide an epidemiological account of elbow and shoulder overuse injuries in youth sports with repetitive overhead action namely Swimming, Badminton, Tennis and Cricket. Methods: 255 participants (187 males, 68 females) aged 8-16 years old were recruited for this study from various organizations. There were 164 swimmers and 91 cricketers. Tennis and Badminton participants could not be recruited. All participants completed a physical questionnaire that would highlight the prevalence of acute injuries and overuse injuries (OP) in the shoulder and elbow areas in the last 6 months. Results: 23% total prevalence of overuse injuries was found in swimming and cricket (22% in the shoulder area and 1% in the elbow area). Comparing between sports, there was a 18% prevalence of shoulder overuse injuries in swimming as compared to a 29% prevalence in cricket. There was a nearly negligible 1% and 2% of prevalence in elbow overuse injuries in swimming and cricket respectively. A total of 59 overuse injuries (56 shoulder, 3 elbow) and 28 were acute injuries (16 shoulder, 12 elbow) were reported. Among gender, age, years of training and hours of training per week, only age was reported to have a significant relationship with the prevalence of overuse injuries (p<0.05). Conclusion: The findings suggest that there is a moderate-high prevalence in shoulder and elbow overuse injuries in youth overhead sports aside from Swimming and Cricket, and the risk will likely increases with training intensity and age.